Strategi Kepemimpinan Pendidikan dalam Pengembangan MAN Propinsi DIY Perspektif Total Quality Management (TQM) - Subiyantoro, Subiyantoro (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
To date, the management of educational empowerment particularly in madrasah (Islamic schools) is still struggling in finding its precise form. The madrasahs are commonly managed base on merely the managers’ personal experience, without proper scientific conception. This happens due to unhealthy condition in which the managers are repressed and burdened by complicated bureaucratic matters. On the other hand, they are also required to compete in ever growing critical society.  The main purpose of this research is to obtain the description of the Islamic educational empowerment strategies based on the Total Quality Management perspective, particularly in light of the educational leadership toward the development of the Madrasah Aliyah Negeri (State Islamic Senior High Schools) in the Province of Yogyakarta. Three methods of data gathering are employed in this research, namely in depth interview, participant observation, and documentation. The results show that, in empowering the Madrasah Aliyah, the leaders 1) rely on personal experience obtained from previous workplace, either being teacher or school principal; 2) perceive comparative study involving educational stakeholders, such as school committee, supervisors, and educational staff at Province level, as an effective tool in developing the madrasahs; 3) attend trainings or workshops held by the ministry of education; and 4) read books related to managerial tasks. Overall, the Total Quality Management can be observed through continuous improvement, culture change, reversed organization, costumers-organization good relationship, focus on costumers and the quality of teaching-learning process.